Structural Evidence for an Octameric Ring Arrangement of SARM1. Issue 19 (6th September 2019) - Sporny, Michael; Guez-Haddad, Julia; Lebendiker, Mario; Ulisse, Valeria; Volf, Allison; Mim, Carsten; Isupov, Michail N.; Opatowsky, Yarden
Abstract: SARM1 induces axonal degeneration in response to various insults and is therefore considered an attractive drug target for the treatment of neuro-degenerative diseases as well as for brain and spinal cord injuries. SARM1 activity depends on the integrity of the protein's SAM domains, as well as on the enzymatic conversion of NAD + to ADPR (ADP Ribose) products by the SARM1's TIR domain. Therefore, inhibition of either SAM or TIR functions may constitute an effective therapeutic strategy. However, there is currently no SARM1-directed therapeutic approach available because of an insufficient structural and mechanistic understanding of this protein. In this study, we found that SARM1 assembles into an octameric ring. This arrangement was not described before in other SAM proteins, but is reminiscent of the apoptosome and inflammasome—well-known apoptotic ring-like oligomers. We show that both SARM1 and the isolated tandem SAM 1–2 domains form octamers in solution, and electron microscopy analysis reveals an octameric ring of SARM1. We determined the crystal structure of SAM 1–2 and found that it also forms a closed octameric ring in the crystal lattice. The SAM 1–2 ring interactions are mediated by complementing "lock and key" hydrophobic grooves and inserts and electrostatic charges between the neighboring protomers. We have mutated several interacting SAM 1–2 interfaces and measured how these mutations affect SARM1 apoptotic activity in cultured cells, and in this way identified critical oligomerization sites that facilitate cell death. These results highlight the importance of oligomerization for SARM1 function and reveal critical epitopes for future targeted drug development. Graphical abstract: In this model for SARM1 structure and mechanism of activation, SARM1 forms an octameric ring. We hypothesize that in the inactive form of SARM1, the enzymatic TIR domains are held apart by the auto-inhibiting ARM domains, and that SARM1 activation (possibly by nicotinamide mononucleotide) involves the release of auto-inhibitory interactions that allows functional dimerization of TIR domains. Unlabelled Image Highlights: SARM1 is arranged as a homo-octameric ring. 2.5-Å resolution crystal structure of the human SARM1 SAM 1-2 domains. The structure reveals a closed octamer ring - an arrangement not described before in other SAM proteins, but reminiscent of the well-known apoptosome and inflammasome. Biochemical and functional experiments demonstrate the importance of SAM 1-2 -mediated oligomers to SARM1 function.